Solution for Islamic Banks Exploitation: A Criticism of Fixed-Yields Based Financing in Indonesia - Ryandono, Muhamad Nafik Hadi (al-Uqud : Journal of Islamic Economics, 2020)
The profit-sharing system is the main characteristic of Islamic banking that distinguishes them from conventional (ribawi) banking. However, in reality, the profit-sharing contract is rarely implemented in Islamic banking. As a result, Islamic banking is still identified as ribawi banking. Many Islamic economists have examined the reasons behind fixed income contracts, especially murabahah contract that applied predominantly, structurally, systematically and massively compared to the profit-sharing contract. Therefore, with a critical analytical approach, this study aims to dismantle and look for solution towards exploitation of fixed income-based financing in Indonesian sharia banking. The results of this study are fixed income-based financing should be applied limited to covering the operational costs of Islamic banks but the remainder must be channelled based on profit-sharing systems. Meanwhile, funding for profit-sharing systems is intended to gain profits and cover the operational cost variables. Thus, predatory exploitation of Islamic banks in Indonesia can be minimized by maintaining the composition of the maximum financing about forty per cent which is a fixed-yield based and leave the rest to a profit-sharing system. Then, the more equitable Islamic bank system and Islamic economic goals will be created and offer benefits such as the achieving of the objectives of Islamic sharia (maqashid shariah) and minimizing the image of Islamic banks as ribawi bank.